Implementasi Etos Kerja Islam pada Karyawan Toko Buah di Jalan Stadion Kabupaten Lumajang - Ahmad Kholilulloh; Muhammad Reza Maulana; Adi Mariyanto; Aniqotuzzuhro' Fitriana (Medan Resource Center, 2023)
This article aims to determine the implementation of the Islamic work ethic in fruit shop employees. This research uses qualitative research techniques with descriptive research types. Data collection methods used are interviews, observation and documentation. Data analysis in this study used triangulation techniques. The results of this study indicate that the Islamic work ethic at the Lumajang fruit shop has been implemented in accordance with the principles of the Islamic work ethic. In line with Toto Tasmara's theory, a Muslim at work should apply the following principles: have a leadership spirit, value time, live frugally and efficiently, and enrich friendship networks. In this case the Islamic work ethic for employees has been well implemented in accordance with the principles of the Islamic work ethic.